PENGARUH IMPLEMENTASI EXPERIENTIAL MARKETING TERHADAP LOYALITAS MEMBER SALON HUMAIRA - Christianingrum, Christianingrum (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2016)
The Development beauty salon industry to grow and properly. Application of the right strategies will be able to retain customers in order to remain defended and loyal to the company in this industry, particularly the Muslim salon. Local customers benefit the company. One effort to keep customers loyal was provided the best deals for consumers, such as giving a unique and memorable experience to customers on every transaction made. This study was conducted to analyze and describe experiential marketing, loyalty in the salon Humaira picture and know how big the influence of experiential marketing to loyalty members Humaira salon. Respondents in this study are members Humaira Tubagus Ismail Beautiful salon. The method used in this research is explanatory survey and descriptive survey. The data used are primary data and secondary data collected through observation, literature study and questionnaire. The hypothesis of this study was “ if the application of experiential marketing is good, then the high customer loyalty," it was tested using path analysis. Results of this research explained that experiential marketing as measured by the dimension of sense, feel, think, act and relate. They were had a positive influence and significant impact on customer loyalty, the overall value of t obtained through the analysis of pathways is greater than t table means the better implementation of experiential marketing Salon Humaira, the higher their loyalty to the salon Humaira.  Keywords: Experiential Marketing, Loyalty